Long‐term effects of the COVID‐19 pandemic on children's physical activity and sedentary behavior - Kristen N. Moore; Bridgette Do; Shirlene D. Wang; Kelsey McAlister; Tiffany M. Chapman; Britni R. Belcher; Genevieve F. Dunton (Obesity Science & Practice, 2024)
Abstract Background During the early months of the COVID‐19 pandemic, decreases in physical activity (PA) and increases in sedentary behavior (SB) were reported among children in the United States (U.S.). This follow‐up analysis examines 13‐month effects of the COVID‐19 pandemic on children's PA and SB one year into the pandemic. Methods Parents of 5–13‐year‐old children in the U.S. (N = 71) reported on their child's PA and SB during the early COVID‐19 period (April‐May 2020) and again 12–14 months later (June‐July 2021). Results Paired t‐tests showed significant within‐subject reductions in SB minutes per day (Mdiff = −86.20, t = 3.26, p < 0.01) but no changes in PA minutes per day. Separate mixed‐model repeated‐measures analysis of covariance procedures found that within‐subject changes in PA and SB did not differ by child sex or age. Conclusion As COVID‐19 restrictions lessened, there were more opportunities for children to reduce SB, but there were still barriers to engage in PA.